Unstructured Socializing With Peers and Delinquency: The Role of Mediation Through the Lens of Akers’ (1998) Social Structure Social Learning Theory of Crime and Deviance - Archer, Robert Joseph Lee (American journal of criminal justice, 2022)
In purview of Akers’ (1998) social structure and social learning (SSSL) theory of crime and deviance, this study explicates the varied processes by which unstructured socializing with peers influences deviance through variables of social learning theory as well as self-control. To examine the proposed processes, data were obtained from 1,354 adjudicated adolescents between the ages of 14 and 18 from the juvenile and adult court systems in Maricopa County, Arizona and Philadelphia County, Pennsylvania. Through use of structural equation modeling, partial support was found for the relationship between unstructured socializing with peers and deviance being partially mediated by differential association, definitions, personal rewards of crime, as well as self-control. By better understanding the multifaceted ways adolescents who spend time in settings of unstructured socializing with friends engage in delinquency, society can better understand the leading factors among youth that occur through socialization resulting in delinquency.